The Effect of Tax Incentives, Tax Socialization, and Taxpayer Understanding on Annual Tax Return Reporting in Sampit City - Yusuf Effendy Julianto; Hendrian Hendrian; Yohanes Juni Pambelum (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to determine the influence of tax incentives, tax socialization, and taxpayer understanding on the reporting of Annual Tax Returns in Sampit City. The sample of this study is Taxpayers in Sampit City, Central Kalimantan with 300 respondents. The purposive sampling method is used related to sample selection. The type of quantitative data is used in this study. The results of this research are that there is no significant influence of tax incentives on the reporting of the Annual Tax Return, but tax socialization, and taxpayer understanding have an effect on the reporting of the Annual Tax Return, which means that the existence of tax incentives does not have a significant effect on increasing compliance in reporting the Annual Tax Return, while tax socialization, and taxpayer understanding have a significant effect on increasing compliance in reporting the Annual Tax Return. In conclusion, the implementation of tax incentive policies does not have a positive effect on the reporting of Annual Tax Returns. In this study, no significant positive influence was found between tax incentive policies on MSME Annual Tax Return Reporting. Although all respondents are taxpayers who have reported the Annual Tax Return and some answered that they are aware of the tax incentives, they generally still pay taxes according to the amount of tax they usually pay in the previous months.